EVALUATION OF CHEMICAL PROPERTIES AND SENSORY OF JELLY CANDY OYSTER MUSHROOMS IN VARIOUS GELATIN CONCENTRATIONS - Sussi Astuti; Dwi Ardiansyah; Susilawati Susilawati (Jurnal Agroindustri, 2021)
The research objective was to obtain the concentration of gelatin as a gelling agent against the sensory and chemical properties of the best white oyster mushroom jelly candy. The treatments, namely gelatin concentrations of 5%, 10%, 15%, 20%, 25%, and 30% were performed 4 times. The study used a completely randomized block design (RAKL) and further test of the least significant difference. The best gelatin concentration was obtained at 20% with a jelly candy product that had a somewhat distinctive flavor of white oyster mushrooms with a score of 2.98, chewy texture, score of 3.89, preferred color score of 3.71, overall acceptance preferred score of 3.8.  Based on SNI, jelly candy meets the standards, namely water content of 18.27% (bb), ash content of 0.25% (bb), reducing sugar 0.28% (bb), and sucrose content of 51.33% (bb).